Design and Analysis of Biomolecular Circuits Engineering Approaches to Systems and Synthetic Biology - Koeppl, Heinz.; Koeppl, Heinz.; Densmore, Douglas.; Densmore, Douglas.; Setti, Gianluca.; Setti, Gianluca.; di Bernardo, Mario.; di Bernardo, Mario. (Springer New York : Imprint: Springer, 2011)
This book is devoted to the design and analysis of biomolecular circuits as considered in systems biology and synthetic biology.  The aim of the book is to present in a coherent framework some of the most recent work on the analysis, simulation and design of biomolecular circuits and systems, reflecting the interdisciplinary and collaborative nature of the field. The results discussed range from how these systems should be modeled and analyzed, to how they should be physically designed and implemented.   Drawing parallels to electronic circuit design, this book’s contents are organized to reflect what the editors believe are the important, necessary steps to build complex synthetic circuits.  Coverage includes analysis and simulation, modularity and abstraction, design and standardization, and enabling technologies. Each of these themes is organized in different chapters that are self-contained so that they can be read individually by experts but also read sequentially by someone wanting to get an overview of the field. This book is intended for computational scientists, e.g. mathematicians, physicists, computer scientist or engineers as well as for researchers from the life sciences. Every effort has been made to make the presentation accessible to a broad, multi-disciplinary audience.